UPAYA MENINGKATKAN MINAT BELAJAR SISWA MELALUI MEDIA AUDIO VISUAL KELAS XI MAS DARUL ULUM - Maryani, Desy; Ulfah, Maria; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aims to improve the performance of economic teachers in an effort to increase students' interest in learning through the visual audio media in the form of videos on employment materials.The method used is a classroom action research method with a descriptive, and collaborative, qualitative approach. The location of the research takes place in MAS Darul Ulum located on Kuala Dua road, Sungai Raya sub-district, Kubu Raya regency especially in XI IPS B class of 15 female students. The data collection techniques used are direct observation techniques. The technique for data analysis used is to calculate averages and percentages. This study is done by the second cycle with results: the ability of teachers to perform learning using visual audio media is 17% increase, which is from 73% in cycle I and increased to 90% in cycle II, and the use of visual audio media could increase students' interest in learning by 20%, which is from 60% in cycle I increasing to 80% in cycle II. From the data obtained it can be concluded that using visual audio media could increase the interest of learning students in employment materials in the XI IPS B MAS Darul Ulum Â Kubu Raya regency.Keywords: Student Learning Interest, Visual Audio Media, and Employment Materials.